'It didn't come up on my radar': an examination of students' orientation toward disability justice in the US. Issue 7 (9th August 2018) - Bialka, Christa S.; Morro, Danielle
Abstract: While social justice is a well-recognized concept, it is less frequently examined through the lens of disability. In order to address existing gaps within social justice education, this qualitative case study investigates how participation in a semester-long Introduction to Disability Studies (IDS) course affected students' orientation toward disability justice, or the conception of disability as an issue of social justice. The framework underpinning this research merges Cipolle's theory of critical consciousness development with disability-based constructs. Findings reveal that participation in IDS allowed participants to develop an awareness of their ability privilege, understand the experiences of peers with disabilities, increase their social awareness of disability, and consider their work as disability allies. This article concludes with recommendations for social justice educators who are interested in applying disability justice practices.